2016
DOI: 10.1186/s12888-016-1071-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender moderates the relationship between childhood abuse and internalizing and substance use disorders later in life: a cross-sectional analysis

Abstract: BackgroundAlthough some studies examined the moderating role of gender in the relationship between childhood maltreatment and mental disorders later in life, a number of them examined the effects of only one or two types of maltreatment on an individual mental disorder, for instance, depression, substance use. It is of considerable clinical and theoretical importance to have in-depth understanding what roles of different types of childhood abuse play out in a wide range of mental disorders among women and men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 42 publications
4
35
1
3
Order By: Relevance
“…As frequently observed, the present investigation revealed that females reported higher levels of depressive symptoms than did males, and, as will be discussed shortly, several predictors of this dimorphism were detected, which is in line with past research (Altemus, Sarvaiya, & Epperson, 2014;Halbreich & Kahn, 2007). Consistent with earlier reports, sexual trauma was more prevalent among females than males (Briere & Elliott, 2003;Maikovich-Fong & Jaffee, 2010;Meng & D'Arcy, 2016;Stoltenborgh, Van Ijzendoorn, Euser, & Bakermans-Kranenburg, 2011;Waal et al, 2017). Although there is limited research concerning sex differences regarding maltreatment and emotional trauma, in the present investigation, these forms of trauma occurred more among females than males.…”
Section: Differences By Sex On Predictor Moderator and Outcome Varisupporting
confidence: 92%
See 1 more Smart Citation
“…As frequently observed, the present investigation revealed that females reported higher levels of depressive symptoms than did males, and, as will be discussed shortly, several predictors of this dimorphism were detected, which is in line with past research (Altemus, Sarvaiya, & Epperson, 2014;Halbreich & Kahn, 2007). Consistent with earlier reports, sexual trauma was more prevalent among females than males (Briere & Elliott, 2003;Maikovich-Fong & Jaffee, 2010;Meng & D'Arcy, 2016;Stoltenborgh, Van Ijzendoorn, Euser, & Bakermans-Kranenburg, 2011;Waal et al, 2017). Although there is limited research concerning sex differences regarding maltreatment and emotional trauma, in the present investigation, these forms of trauma occurred more among females than males.…”
Section: Differences By Sex On Predictor Moderator and Outcome Varisupporting
confidence: 92%
“…Although there is limited research concerning sex differences regarding maltreatment and emotional trauma, in the present investigation, these forms of trauma occurred more among females than males. Significant sex differences in physical abuse was not observed, which is in line with earlier research (Briere & Elliott, 2003), although the majority of studies indicated that males experienced more physical abuse during childhood than did females (Meng & D'Arcy, 2016;Thompson, Kingree, & Desai, 2004).…”
Section: Differences By Sex On Predictor Moderator and Outcome Varisupporting
confidence: 89%
“…Childhood maltreatment has repeatedly been shown to have a negative impact on mental health outcomes in adulthood [1,2]. For example, it increases the risk of psychiatric disorders such as depression [1,[3][4][5], bipolar disorder [6], post-traumatic stress disorder [1,4] and suicide attempts [1,4], as well as alcohol use disorder (AUD) [1,3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of pa-tients with AUD have mostly focused on sexual and physical abuse [2,4,7,[12][13][14][15]. It has been proposed that emotional abuse has received less attention due to difficulties in defining and identifying the concept of emotional abuse, as well as the fact that it is not considered a crime [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation